Reduced Expression of Hippocampal GluN2A-NMDAR Increases Seizure Susceptibility and Causes Deficits in Contextual Memory - Acutain, Maria Florencia; Griebler Luft, Jordana; Vazquez, Cecila Alejandra; Popik, Bruno; Cercato, Magalí C.; Epstein, Alberto; Salvetti, Anna; Jerusalinsky, Diana A.; de Oliveira Alvares, Lucas; Baez, Maria Verónica (Frontiers in Neuroscience, 2021)
NMDA receptors are heterotetramers composed of two GluN1 obligatory subunits and two regulatory subunits. In cognitive-related brain structures, GluN2A and GluN2B are the most abundant regulatory subunits, and their expression is subjected to tight regulation. During development, GluN2B expression is characteristic of immature synapses while GluN2A is present in mature ones. This change in expression induces a shift in GluN2A/GluN2B ratio known as developmental switch. Moreover, modifications in this relationship have been associated with learning and memory as well as different pathologies. In this work, we used a specific shRNA to induce a reduction in GluN2A expression after the developmental switch, both, in vitro in primary cultured hippocampal neurons and in vivo in adult male Wistar rats. After in vitro characterization, we performed a cognitive profile and evaluated seizure susceptibility in vivo. Our in vitro results showed that the decrease in the expression of GluN2A changes GluN2A/GluN2B ratio without altering the expression of other regulatory subunits. Moreover, rats expressing the anti GluN2A shRNA in vivo displayed an impaired contextual fear-conditioning memory. In addition, these animals showed increased seizure susceptibility, in terms of both time and intensity, which led us to conclude that deregulation in GluN2A expression at the hippocampus is associated with seizure susceptibility and learning-memory mechanisms.